Understanding Binary Options in the Context of Trading Law in the Digital Era - Syam'un Syam'un; Sardjana Orba Manullang; Tamaulina Br Sembiring; Irma Rachmawati Maruf; Prasetyono Hendriarto (Budapest International Research and Critics University, 2022)
This paper examined various information content to gain an in-depth understanding of the status or law of Binary Options in Indonesia's trading context. In recent years, the development of digital-based businesses has been growing and proliferating, thus requiring an explanation of the legal status in business and trade. Therefore, we have obtained research evidence that provides a comprehensive understanding of the existence of binary options and their legal status. Before concluding, of course, we need a scientific data processing process to account for these findings regarding the validity and reliability of these findings. As for the process, we get the data through a Google search on some sources of binary business literature and legality both in the Indonesian context and internationally. So, based on the results of the study and discussion, we can conclude that the legal status of binary options trading is a business that is forbidden due to the nature of its work is highly speculative or chancy, and this is not in line with the context of the legal status in Indonesia. It is hoped that these findings will add to the repertoire of scientific understanding of business and trade in Indonesia, especially in the digital era.